Answer:
Divide the b parameter by 2 and rewrite it as the square of a binomial inserting the x, and the c as the half of b.
.[tex]x^{2}+14x+49= (x+7)^{2}[/tex]
Step-by-step explanation:
1) Every perfect square trinomial can be written as the square of a binomial. For instance:
[tex]x^{2}+8x+16 = (x+4)^{2}\\x^{2}-7x+49=(x-7)^{2}\\x^{2}+24x+144= (x+12)^{2}[/tex]
2) Firstly let's complete the square
2a. Find "c", the constant term by dividing "b"
[tex]x^{2}+14x\Rightarrow x^{2}+14x+7 [/tex]
2b. Square it
[tex]x^{2}+14x+7^{2} [/tex]
3) Since we completed the square, then to write that trinomial as the square of a binomial :
Divide the b parameter by 2 and rewrite it as the square of a binomial inserting the x, and the c as the half of b.
.[tex]x^{2}+14x+49= (x+7)^{2}[/tex]